Rickettsial Infection amongst Febrile Illness Patient in a Tertiary Care Hospital: A Retrospective Cross-sectional Study - Gurung, R. B.; Gurung, R. B.; Sapkota, P.; Bhatt, S.; Tamang, A.; Joshi, S.; Khadka, S.; Jaisy, D. N.; Chalise, S.; Shrestha, P. (Kathmandu University Medical Journal, 2022)
Background Rickettsial infection is an emerging neglected tropical disease in the Southeast Asia. In past few years Nepal is also reporting escalating prevalence of rickettsia. The under evaluation is resulting it as undiagnosed or are simply labeled as pyrexia of unknown origin. Objective To find out the prevalence of rickettsia in a hospital setting, assess the sociodemographic and other relevant clinical features of the rickettsia patients. Method This is a hospital based retrospective cross-sectional study from October 2020 to October 2021. This study reviewed the medical records of the department. Result The study included 105 eligible patients and the prevalence rate was 4.38 per 100 patients. The mean age of the participants was 42 years, and the mean hospital stay was 3 (SD ±2.06) days. More than 55% of the participants had fever for less than or equal to 5 days and 9% had Eschar present. Vomiting, headache, and myalgia were the most common symptoms and hypertension, and diabetes were the common comorbidities. Pneumonia and the acute kidney injury were the two complications of the patients as stated in the study. The severity of the thrombocytopenia deducted from admission time to discharge, and the case fatality was 4%. Conclusion The future studies shall consider on collaborative clinical and entomological research. This would help in better understanding of the etiology of supposedly unknown febrile illness and the under-investigated field of emerging rickettsia in Nepal.